The effects of oral and written meta-linguistic feedback on ESL students writing - Kobra Mansourizadeh,; Khairi Izwan Abdullah, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Research on corrective feedback has shown the beneficial effects of improving accuracy in writing though more research is being done on the effectiveness of different types of corrective feedback and the intervening variables. In line with this trend of research, this study was designed to investigate the effects of written and oral meta-linguistic feedback on the accuracy of subject-verb agreement in the writings of 47 undergraduate students. There were three groups in the study: Written Group, Oral Group and Interactional Group. The Written Group received direct error correction in combination with written meta-linguistic feedback. The Oral Group received direct error correction in combination with oral meta-linguistic feedback and the Interactional Group received direct error correction in combination with oral meta-linguistic feedback and also was involved in an interactional activity (discussion on their errors). The results demonstrated that all three groups improved their writing accuracy in the post-test as the result of receiving meta-linguistic feedback, but the Oral Group outperformed the other two groups. The findings of this study provided further evidence in support of the significant effects of corrective feedback especially oral meta-linguistic feedback which is both practical and time-saving.